The Effect of Product Quality, Brand Image, and Competitive Prices on Purchasing Decisions - riawan, joni; Jonathan, Dyson (TECHBUS (Technology Business and Entrepreneurship), 2025)
This study aims to examine and analyze the influence of product quality, brand image, and price on purchasing decisions at CW Coffee. The research employed a quantitative approach, with data collected through an online questionnaire distributed via Google Forms. The population in this study consisted of Indonesian consumers who had previously purchased CW Coffee products. The sample was selected using a convenience sampling technique, resulting in a total of 98 respondents. The findings indicate that product quality and price have a significant influence on purchasing decisions, while brand image does not show a significant effect. Based on these results, it is recommended that CW Coffee continue to improve product quality and maintain a competitive pricing strategy, as both factors play a crucial role in influencing consumer purchase decisions. Although brand image was not found to be a significant factor in this study, it is still advisable for CW Coffee to preserve and strengthen its brand identity to support long-term marketing efforts.